Synthesis and antibacterial activities of some 1,2,4-triazole derivatives - (:unkn) unknown (My University, 1999)
Reactrions of 3-amino-1,2,4-triazole with some dicarboxylic acid anhydrides and diketones were studied. The structural assignments of the compounds obtained from the reactions are based on elemental analyses and spectral data. The compounds were screened for their in vitro antibacterial activities.
Keywords: 1,2,4-Triazole; 3-Amino-1,2,4-triazole; Antibacterial activity; Dicarboxylic acid anhydrides; Diketones; Synthesis